Discovering Key Success Factors of Mid-Star Hotels During a Pandemic - Tasya Sierends Devana; Nathanael Christianto; Tasha Devina Christianto; James Christian Setjoadi; Vincent Vincent; Handyanto Widjojo (Universitas Prasetiya Mulya, 2022)
The objective of this research is to discover the factors that influence consumers’ interest in staying at mid-star hotels during the COVID-19 pandemic. A mixed-methods approach combining qualitative and quantitative research was applied. Data from 206 respondents was collected through online surveys that were processed through regression analysis. The findings show three factors that positively and significantly influence consumers’ interest to use mid-star hotels during the pandemic: cleanliness, health protocol, and facilities. Meanwhile, the promotion does not significantly affect the dependent variable. This research could provide insight into the hotel industry, specifically mid-star hotels, to consider and apply those factors into their priorities so that they can generate greater consumer interest in staying at mid-star hotels mid- and post-pandemic.